KETAHANAN MULUR DAN OKSIDASI SIKLIK BAJA SUS 304 HASIL PELAPISAN METAL MATRIX COMPOSITE NiCr+Cr3C2 DENGAN METODA HVOF - Naufal, Muhammad Luthfi; Waldi, Muhammad; Prajitno, Djoko Hadi (Urania: Jurnal Ilmiah Daur Bahan Bakar Nuklir, 2024)
CREEP AND CYCLIC OXIDATION RESISTANCE OF SUS 304 STEEL AFTER COATING WITH METAL MATRIX COMPOSITE NiCr+Cr3C2 BY HVOF METHOD. Deposition of 60% NiCr + 30% Cr3C2 + 10% Al2O3 and 60% NiCr + 40% Cr3C2 metal matrix composite coating has been done on SUS 304 steel surface by the High Velocity Oxygen Fuel (HVOF) Thermal Spray Coating technique. The purpose of the coating was to improve SUS 304 steel creep resistance and cyclic oxidation on boiler tubes of steam power plant application. The treatments include creep test at 550oC with a load of 0.4 and 0.6 σy (yield strength) for 30240 minutes (21 days), cylclic oxidation with various temperatures of 600, 700 dan 800oC in tubes furnace for 1 hour and cooling for 15 minute in 1cycle. Measurement was done every one cycle to observe weight change of the oxide, and themeasurement was done for 5 cycles. The recommended coating specimen for boiler tubes of steam power plant application is coating specimen of 3 three components of MMC with the lowest creeprate of 0.000148917 %/hour and cyclic oxidation resistance at 600o (which has a lowest change inoxide weight, coating thickness and oxide compounds formed on coating).